RESPON IKAN KARANG PADA AREA APARTEMEN IKAN DI PERAIRAN TOBOLOLO DAN GAMALAMA KOTA TERNATE - Aditiyawan Ahmad (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
Fish apartment is a management actions to maintain the presence of coral fish that serves as a new habitat well as shelter and spawning. The number of fish apartment at each location is 20 units. The present study aimed at assessment the response of coral fish to the fish apartment based on the species and number of individuals coral fish. Total species found in the area of fish apartment as much as 7 families and 9 species with a total of 241 individual coral fish in the Tobololo, while 12 families and 23 species with a total of 567 individual. Moreover, the juvenile of coral fish is not identified with a size of 2-3 cm, the number of individuals in Tobololo 154 and 275 in Gamalama. The response of coral fish positively to the fish apartment evidenced by an increase in abundance and the percentage of the number and types of coral fish. So that management action with fish apartment approach provides a positive impact on the presence of coral fish as a new habitat and supports the corals juvenile.